John Dewey’in Türkiye eğitim sistemine etkileri - Gül, Veysel (My University, 2003)
Bu araştırmanın konusu, pragmatist felsefesinin kurucularından ve en önemli fikir babası olan John Dewey’in eğtim ile ilgili görüşlerinin analizi ve ülkemiz Milli Eğitim Bakanlığının daveti üzerine hazırladığı raporu doğrultusunda ortaya koyduğu önerilerin Türk eğitim sistemine yaptığı etki ve değişimleri tespit etmektir. Bu araştırma, Jonh Dewey’in ülkemize çağrıldıı ve yaptığı bir takım incelemeler doğrultusunda birçok atılım, değişim ve yeniliklerin yapıldığı 1954 yılları arasında dönem ile sınırlandırılmıştır. Konuyla ilgili olarak literatür taranmış ve literatüre adaylı olarak birincil kaynaklara ulaşılmıştır. Elde edilen verilerle John Dewey’in raporunda sunduğu öneriler doğrultusunda Türk eğitim sisteminde birçok alanda köklü değişiklikler yapılmıştır. Özellikle öğretmen yetiştiren kurumlar olan Öğretmen Okullarında ve köye uygun, köylerin eğitim ve yaşam tarzına yönelik Köy enstitülerinin açılmasında John Dewey’in sunduğu raporun etkileri tespit edilmiştir. The subject of this research is the analysis of the thoughts of John Dewey who is the founder of pragmatist philosophy about education and the determaniton of the effects and changes that his report which he has prepared on the invitation of our ministry of education has on Turkish educational system. This research is limited with the period between the invitation of John Dewey and the report-which he presented to ministry of education that he has prepared accourding to the resalts of his studies in 1924 and 1954 when several progresses, changes and renewals were made according to this report. Literature is scanned about the subjict and primary sount are reached conneccted with literature with the data that has been reached according to the suggestions that John Dewey has presented in his report, several radical cahges have been made in several areas of Turkish educational system. The effects of John Dewey’s report on the opening of especially the scholls of teacchers that train people to be teachers and the teachers trainning institutions suitable for the education and life style of the villages.
Keywords: Eğitim